2010
DOI: 10.1007/s00125-010-1802-0
|View full text |Cite
|
Sign up to set email alerts
|

QT interval prolongation during spontaneous episodes of hypoglycaemia in type 1 diabetes: the impact of heart rate correction

Abstract: Aims/hypothesis Prolongation of the heart rate corrected QT interval (QTc) is seen during episodes of hypoglycaemia in type 1 diabetes. We studied the relationship between spontaneous hypoglycaemia and the QT interval and hypothesised that the choice of heart rate correction affects the observed change in QTc. Methods Twenty-one participants with type 1 diabetes (aged 58±10 years with duration of diabetes 34±12 years) had continuous glucose and ECG monitoring for 72 h. QT and RR intervals were measured during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 24 publications
6
34
0
Order By: Relevance
“…Recently, several studies have reported an association between hypoglycemia and QT prolongation (11)(12)(13), which reflects abnormal cardiac repolarization and may be a marker of increased mortality in T1DM patients (32). The results of the current study demonstrated that not only T1DM patients but also many T2DM patients exhibited an abnormal QT prolongation during severe hypoglycemia.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Recently, several studies have reported an association between hypoglycemia and QT prolongation (11)(12)(13), which reflects abnormal cardiac repolarization and may be a marker of increased mortality in T1DM patients (32). The results of the current study demonstrated that not only T1DM patients but also many T2DM patients exhibited an abnormal QT prolongation during severe hypoglycemia.…”
Section: Discussionsupporting
confidence: 60%
“…1. The median GCS scores in the T1DM and T2DM group were 12 (9-14) and 11 (7)(8)(9)(10)(11)(12)(13)(14), respectively (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bazett formula corrects intervals to a rate of 60 bpm and tends to result in overcorrection at high heart rates and undercorrection at lower heart rates. Nevertheless, it is generally considered a reasonably accurate correction in the setting of hypoglycemia (36). In our study we detected a mean QTc prolongation of 5 ms during nocturnal hypoglycemia and 12 ms during daytime hypoglycemia in comparison with matched euglycemia.…”
Section: Discussionsupporting
confidence: 57%
“…This distinction is important because unlike rodents, patients with t1DM do not exhibit heart rate corrected QT-interval prolongation in the absence of confounding factors, such as diabetic ketoacidosis (24) or spontaneous hypoglycemia (11). Clinically, these additional stimuli are required to unmask pathological QT-interval prolongation in patients with t1DM (11,14,17,24).More importantly, most EP studies in t1DM have been performed in animal models that exhibited highly artificial rises (Ͼ300%) in blood glucose levels that are well beyond what is commonly encountered in patients with diabetes (20,33,36,40,46). Such extreme levels of hyperglycemia, which are known to affect ion channels, preclude the direct translation of some of these earlier findings to humans.…”
mentioning
confidence: 93%